Effects of yttria doping on the interfacial reaction between barium zirconate ceramics and TiAl alloy melt - Yun Shen; Du Hong; Tianfang Sun; Rui Hou; Gong Zheng; Yaran Niu; Guang Chen (Journal of Asian Ceramic Societies)
BaZr1-xYxO3-δ (x = 0, 0.04, 0.08, 0.12) crucibles with doping different contents of Y2O3 were prepared by the pressureless sintering method, and the interfacial reaction behaviors in TiAl alloy melt was investigated using vacuum induction melting. The results revealed that the BaZrO3 ceramics contained a small amount of monoclinic ZrO2 and Ba-rich areas. With increasing Y2O3 doping content, yttrium-rich cubic ZrO2 instead of monoclinic ZrO2 generated and the average grain size decreased significantly. The results after melting showed that the thickness of the reaction layer of the BaZr1-xYxO3-δ decreased from hundreds of microns to tens of microns with the increase of the Y2O3 content. Moreover, the zirconium content in the alloy decreased. Overall, the BaZr0.96Y0.04O3-δ ceramic crucible had a small thickness of the reaction layer and slight oxygen contamination in the alloys. This study offers new insights for the further development of Y2O3-doped BaZrO3 ceramics used in melting TiAl alloys.